2017
DOI: 10.1113/ep086434
|View full text |Cite
|
Sign up to set email alerts
|

The role of the blood–brain barrier in hypertension

Abstract: What is the topic of this review? This review highlights the importance of the blood-brain barrier in the context of diseases involving autonomic dysfunction, such as hypertension and heart failure. What advances does it highlight? It highlights the potential role of pro-inflammatory cytokines, leucocytes and angiotensin II in disrupting the blood-brain barrier in cardiovascular diseases. Advances are highlighted in our understanding of neurovascular unit cells, astrocytes and microglia, with a specific emphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 32 publications
2
50
0
1
Order By: Relevance
“…The BBB permeability can be affected by a plethora of factors such as viral and bacterial infection, traumatic brain injury, poisoning, or hypertension . Interestingly, it seems that factors from the gut microbiota can also affect BBB permeability, because germ‐free or antibiotic‐treated mice show an increased BBB permeability and altered expression of tight junction proteins .…”
Section: Introductionmentioning
confidence: 99%
“…The BBB permeability can be affected by a plethora of factors such as viral and bacterial infection, traumatic brain injury, poisoning, or hypertension . Interestingly, it seems that factors from the gut microbiota can also affect BBB permeability, because germ‐free or antibiotic‐treated mice show an increased BBB permeability and altered expression of tight junction proteins .…”
Section: Introductionmentioning
confidence: 99%
“…Microvessel culture studies have shown that AT1R activation increases BBB permeability [44,45]. Inflammatory IL-1β, and TNF-α, which are shown to increase in the circulation of RVH rats also disrupt the integrity of BBB [46,47]. Another mechanism that damages the BBB in RVH is the disintegration of adventitia layer in the cerebral vascular endothelium by MMP enzymes, which are activated by inadequate cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 may bind to its receptor Angiotensin Converting Enzyme 2 (ACE2) expressed in endothelial cells of cerebral capillaries (Peña Silva et al 2012), and within the brain parenchyma in both neurons and microglia (Yamagata et al 2020). Since the blood-brain barrier is disrupted in hypertension (Setiadi et al 2018) and hypertension is a frequent comorbidity for COVID-19, these patients may have a higher risk of cerebral complications.…”
Section: Sars-cov-2 Injures the Brainmentioning
confidence: 99%